OPTIMIZING PRODUCT QUALITY THROUGH INTEGRATING QUALITY CONTROL METHODS - Emmalia Adriantantri; Sri Indriani (Computer Science Department, Malang National Institute of Technology, 2024)
Industrial developments are currently increasingly competitive, so business people need to produce quality products at affordable prices and be able to meet customer demand in a timely manner. To produce quality products, the production process must really pay attention to and fulfill quality aspects so that it can reduce the number of product defects and wasted production costs. All production process activities that do not have added value must be eliminated, because they have an impact on production costs and company income. In connection with this, industry needs to carry out good quality control in its production process in order to achieve optimal product quality improvement or improvement. A Quality Control System is an effort to improve and enhance the quality, productivity and performance of an industry so that it can achieve optimal results. The Quality Control System aims to utilize all existing assets to improve quality. There are many methods that can be used to improve quality. For this reason, research needs to be carried out to obtain a formula for combining the methods contained in inventory control in order to obtain optimal product quality improvement. The aim of this research is to model a product quality optimization system, to optimize costs and the level of profit obtained. The method used is the PDCA cycle, the Six Sigma method with seven basic tools and the SQC approach, Failure Mode Effect Analysis (FMEA) and 5W + 1H